Observation facts of the associated surgical clinic and radiotherapy: tissue pathophysiology in large surgical decorations. Meiopragia before the action of the rays. Human regional cancerization comparable to experimental - Stajano, Carlos (Cirugía del Uruguay, 2020)
Presented at session 8th August 1945